Data science in educational assessment - Gibson, David; Webb, M. (Springer New York LLC, 2015)
This article is the second of two articles in this special issue that were developed following discussions of the Assessment Working Group at EDUsummIT 2013. The article extends the analysis of assessments of collaborative problem solving (CPS) to examine the significance of the data concerning this complex assessment problem and then for educational assessment more broadly. The article discusses four measurement challenges of data science or ‘big data’ in educational assessments that are enabled by technology: 1. Dealing with change over time via time-based data. 2. How a digital performance space’s relationships interact with learner actions, communications and products. 3. How layers of interpretation are formed from translations of atomistic data into meaningful larger units suitable for making inferences about what someone knows and can do. 4. How to represent the dynamics of interactions between and among learners who are being assessed by their interactions with each other as well as with digital resources and agents in digital performance spaces. Because of the movement from paper-based tests to online learning, and in order to make progress on these challenges, the authors call for the restructuring of training of the next generation of researchers and psychometricians to specialize in data science in technology enabled assessments.